(untitled) (Journal of the Bangladesh Agricultural University, 2024)
The freezing technique has been used for thousands of years for the preservation of meat. The frozen meat has to be thawed before further processing. Quality deterioration occurs during the thawing process. The uniform-sized broiler chicken samples were individually frozen using an ultra-low temperature freezer (-40°C) for an overnight. The frozen meat samples were thawed in the refrigerator (4°C), cool room (20°C), hot air oven (60°C), tap water (27±5°C), and hot water conditions (40°C) until core temperature of the meat reaches 10°C in all method except refrigeration method where the core allowed to reach 4°C. Moisture content (MC), water holding capacity (WHC), drip loss (DL), cooking loss (CL), and pH were determined. There were significant differences (p<0.05) observed among the quality parameters of the samples, including MC, DL and CL based on the different thawing methods. However, there were no significant deviations in the pH and WHC. The sensory evaluation was also carried to evaluate color, taste, flavor, chewiness, juiciness and overall rating of the uniformly cooked samples by using nine hedonic scale techniques. There were no significant differences among sensory parameters of the samples (p<0.05). Of which, the highest rating was obtained for the cool room and tap water method, while the poor rating was for the refrigeration method. Therefore, the different thawing methods impact on the quality parameters of the frozen broiler chicken rather than influencing the sensory qualities. However, the cool room thawing method had minimized reductions in the qualities of the thawed broiler chicken followed by the tap water method. J Bangladesh Agril Univ 19(1): 78–84, 2021 https://doi.org/10.5455/JBAU.23371